(untitled) (Journal of Educational Sciences, 2025)
This article provides a brief analysis of the current state of the training process for mountaineers in the Republic of Kazakhstan and the city of Almaty, aimed at developing endurance. During the analysis, several problematic areas were identified, and solutions were proposed. One of the methods suggested by the authors involved conducting an experiment. A methodology was modeled, which is expected to improve general and specific endurance in mountaineers of initial training levels (IT) through modifications to the general physical training system. The methodology includes the integration of three elements into the training process: (1) specific running exercises performed on moderate inclines (up to 10-15°), (2) accelerations on moderate inclines (15°), and (3) interval accelerations on moderate inclines (15-20°), performed in mid-altitude conditions. Key words: mountaineering, endurance, high-altitude conditions, physical training.